PARADIGMA BARU MENGEMAS DAKWAH MELALUI MEDIA TELEVISI DI ERA GLOBALISASI - Fatmawati Fatmawati (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2010)
Propagation through the medium of television in this era of globalization has an important role in development,particularly in the development of character, morals and character. Television media should repacking propagandaprogram with a new paradigm which adopted the five basic elements: First, as an information center for all levels of society.Second, as a medium of education and teaching and socializing role of religious values, thus encouraging the birth of theknowledgeable Muslim. Third, mission packaged with an interactive method to provide quick and precise solutions to thecommunity. Fourth, as a counterweight events that are less educate, especially programs that embody foreign culture dueto globalization. Fifth, the television can become the economic and social development of Islamic society by creating amarketable da'wah programs such as talk shows, soap operas religious.